HUBUNGAN RESTRUKTURISASI PERJANJIAN PEMBIAYAAN KONSUMEN SEPEDA MOTOR DENGAN POJK NO.11/POJK.03/2020 TENTANG STIMULUS PEREKONOMIAN NASIONAL - rohani, aceng asnawi; Gunawati, Anne; PS, Agus Prihartono (Legal Standing : Jurnal Ilmu Hukum, 2021)
The government enforces various kinds of regulations in providing protection to the public, one of which is through the Financial Services Authority (OJK) by issuing POJK Number 11 / POJK.03 / 2020 concerning National Economic Stimulus as a Countercyclical Policy on the Impact of the Spread of Coronavirus Disease 2019. This regulates the implementation of the relaxation policy. against debtors affected by the new Corona Virus or Covid-19 outbreak. The restructuring carried out by the financing institution is carried out in accordance with the guidelines issued by the OJK based on POJK Number 11 / POJK.03 / 2020. However, the implementation is left to the policies of each financing institution, the relief scheme may vary, among others, in the form of lowering interest rates, adjusting principal or interest installments, extension of time or other matters determined by the bank or financing institution. This regulation does not regulate sanctions against banks / financing companies that do not provide restructuring / relaxation programs for debtor customers, because they are not coercive, the language used in this POJK is "can" not "must".